Proceedings of 2013 IEEE International Conference on Teaching, Assessment and Learning for Engineering (TALE) 2013
DOI: 10.1109/tale.2013.6654388
|View full text |Cite
|
Sign up to set email alerts
|

Steps to increase student engagement and retention in first year engineering

Abstract: This paper details the changes undertaken to the introductory Bachelor of Engineering (BE) course Foundations of Engineering (ENGR101) at Victoria University, Wellington, New Zealand (VUW) to improve first year student engineering experience. A requirement of the BE is that a student obtains a B average over their core papers in Part I to progress with the degree. The paper also reports on student reactions to these changes based on information gained from surveys. It finds the introduced changes in 2011 incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…According to the research presented by Rodrí-guez-Gómez, Meneses, Gairín, Feixas & Muñoz (2016), many of students change to a different area of knowledge, showing the inefficient guidance systems and university entrance. Some successful attempts to increase the first year success are presented in the literature (Boath et al, 2016;Watterson, Browne & Carnegie, 2013;Wood, GrayGanter & Bailey, 2016). The increase of first year retention will result in decreasing number of inactive students and consequently in lower costs of the study.…”
Section: Discussionmentioning
confidence: 99%
“…According to the research presented by Rodrí-guez-Gómez, Meneses, Gairín, Feixas & Muñoz (2016), many of students change to a different area of knowledge, showing the inefficient guidance systems and university entrance. Some successful attempts to increase the first year success are presented in the literature (Boath et al, 2016;Watterson, Browne & Carnegie, 2013;Wood, GrayGanter & Bailey, 2016). The increase of first year retention will result in decreasing number of inactive students and consequently in lower costs of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, cognitive engagement relies on the principles of use and effort to invest in learning activities [3], [15], which may help students use the application. Besides a relationship among students' behavioral engagement, cognitive engagement, and educational app engagement, for both pre-engagement and changes in engagement, we observed that changes in engagement negatively impact students' app engagement.…”
Section: Resultsmentioning
confidence: 99%
“…Students' engagement is considered a fundamental motivational construct in engineering education and is often associated with learning and experience [1], [2], [3]. Existing literature has defined students' engagement differently depending on the context of its use, where most researchers have discussed engagement with an explicit link to students' academic activities and tasks [4].…”
Section: Introductionmentioning
confidence: 99%